Perspektif Mahasiswa Jurusan Matematika Kelas Kimia Umum terhadap Pemanfaatan Bunga Telang dan Cuka sebagai Tinta Alami Ramah Lingkungan - Dimas Ridho; Tita Juwitaningsih; Nadhira Eka Putri Prayudi; Nabila Mutiara Syifa; Putri Syahbilah; Fitrah Ifandi Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the perspectives of mathematics students in general chemistry classes. on the use of butterfly pea flowers (Clitoria ternatea) and vinegar as basic ingredients for making environmentally friendly natural ink. This innovation is expected to be an alternative to the use of chemical inks and to encourage environmental awareness among students. This study uses a descriptive analysis method with data collection through questionnaires distributed to students. The results of the analysis show that most students gave a positive response to the use of butterfly pea flowers and vinegar as natural ink, especially in terms of loss, material safety, and potential application in the campus environment. These findings indicate an opportunity to develop environmentally friendly products based on local wisdom in the world of education.